Gaya Bahasa Kiasan Dalam Puisi â€œMansyÅ«rÄtun FidÄiyyatun â€˜AlÄ JudrÄni IsrÄÄ«lâ€ - A'yun, Loita Kurrota (Institut Agama Islam Negeri (IAIN) Curup, 2018)
A poet often uses the style of language in composing poetry in order to achieve the desired beauty. Likewise with one of the famous Arab poets in the modern era, namely Nizar Qabbani. He often uses language styles, one of which is the figurative language style, to compose verses in his poems. One of his works which contains a lot of this style of figurative language is his poem entitled